Job preservation by an office worker with idiopathic cervical dystonia: case report - Gallozzi, Alessia; Panigazzi, Monica; Scafa, Fabrizio; Capodaglio, Edda Maria; Candura, Stefano Massimo (La Medicina del Lavoro, 2020)
Background: Work preservation is a main goal in the rehabilitation of chronic disabling diseases. We describe the application of an interdisciplinary protocol, involving the occupational physician, the occupational therapist and the ergonomist, in the case of a 50 year-old office worker with idiopathic cervical dystonia, a movement disorder that can seriously impair work capability. Case report: The disease was diagnosed at age 25, and subsequently worsened. The man presented postural difficulties and pain. The symptomatology worsened during working shifts, preventing him from doing his job properly. Functional evaluation and ergonomic inspection of the office environment led to the correction of evident critical inadequacies. This allowed the patient to continue working in correct conditions, resulting in improvement of his global health status. Conclusions: The interdisciplinary rehabilitative approach here described may allow subjects with idiopathic cervical dystonia to keep their jobs by adapting the workplace to the changed physical capabilities.